Effect of Challenge Feeding on Prepartum and Postpartum Dry Matter Intake in Sahiwal Cattle in the Arid Region of Rajasthan - Singh, Vikramjit; Goswami, Subhas Chander; Jhirwal, Arunr Kumar; Choudhary, Vijay Kumar; Choudhary, Mohan Lal (Indian Journal of Animal Nutrition, 2020)
The present study was carried out with the objective of investigating the effect of challenge feeding on prepartum and postpartum dry matter intake in Sahiwal cattle. The present study was conducted on eighteen healthy, advance pregnant Sahiwal cattle from 60 days prepartum to 120 days postpartum. The animals were divided into two groups i.e. control and treatment on the basis of milk yield, parity and body weight. The animals in control group were given standard ration while in challenge fed (treatment) group, the animals were given additional amount of concentrate mixture. Both the groups were offered ad libitum dry fodder during entire period of study. The mean DMI (kg) in control and treatment group cows during prepartum period was 8.37 ± 0.35 and 9.34 ± 0.36 kg/d, respectively which did not differ significantly between treatments. The postpartum DMI was significantly higher (P<0.05) in treatment group (11.04 ± 0.10 kg) as compared to control group (9.38 ± 0.06 kg).